PROPOSED OF MARKETING STRATEGY FOR OUTSOURCING BUSINESS AT PT. PELINDO DAYA SEJAHTERA (The Indonesian Journal of Business Administration, 2019)
Most of the companies over the past decade has sent some of their job function usually a non-core job, to other parties with the intention of focusing the company’s growth and win the business competition. These activities called an outsourcing activity and its already become a global trend recently since it creates a new specific market demands and business opportunities. The outsourcing company still interesting the Domestic market to be developed and marketed, likewise PT Pelindo Daya Sejahtera (PT PDS), as a PT Pelindo III’s subsidiaries company, PT PDS was established to manage contract workers in PT Pelindo III who already have work competencies in port industries. PT PDS’s Market Size still dominate with PT Pelindo III Group (Captive Market) as much as > 99% while the external market only < 1%.Whereas, the external outsourcing market for a non-core job activity, both in Port Industries nor general industries outside Pelindo III Group are still potentially captured by PT PDS, but it still can not be captured by PT PDS.The thesis is organized to analyze the Marketing Strategy that will be implemented and run by PT PDS in order to expand the market size especially the External Market. In formulating a possible strategy in PT PDS, are using the analysis tools namely PESTEL, Porter's Five Forces, Competitor Analysis and Market Analysis for company's external factors and as a company's internal factors analysis will be using a value of chains analysis and resources analysis. The proposed of product strategy in expanding PT PDS external market is the recommendations as results of the analysis that has been done and will set into an action plan that will be executed by PT PDS. Based on this action plan, then the timetable and planning resources are arranged.Keywords: an outsourcing business, internal market, the external market, market size, marketing strategy